A Chlorotoxin‐Directed Diselenide‐Bridged Tumor‐Homing Persistent Luminescence Nanoprobes Mediating Inhibition of Oxidative Phosphorylation for Long‐Term Near‐Infrared Imaging and Therapy of Glioblastoma. (19th September 2022) - Kong, Jianglong; Sun, Yuting; Ge, Xiaohan; Mao, Meiru; Yu, Hongrui; Wang, Yi
Abstract: Glioblastoma (GBM) is the most prevailing malignant primary brain tumor, and the precise diagnosis of GBM has always been a challenge. Gboxin is a recently developed drug efficiently inhibiting the oxidative phosphorylation in GBM cells, and both the chlorotoxin (CLTX) and GBM cell membrane coating are capable of GBM targeting and tumor homing. Herein, the near‐infrared (NIR) persistent luminescence (PL) nanoparticle, CUDZG, with a dual function of imaging and therapy is developed based on ZnGa2 O4 :Cr 3+, Sn 4+ . CUDZG exhibits superior rechargeable NIR PL for at least 48 h with excellent tissue penetration in vivo, which enables the longstanding autofluorescence‐free imaging of the orthotopic GBM. The tumor growth of both the orthotropic and subcutaneous GBM‐bearing mice are significantly suppressed by CUDZG. This is the first‐time report of 1) the integration of CLTX and cell membrane coating for drug delivery, 2) diselenide‐based trigger release for anti‐GBM therapy, and 3) the systemic delivery of Gboxin. This study also offers an example of the highly promising blood‐brain penetrable drug carriers for precise diagnosis and therapy of central nervous system diseases. Abstract : A near‐infrared (NIR) persistent luminescence (PL) nanoparticle, CUDZG, with a dual function of imaging and therapy is developed. CUDZG exhibits superior rechargeable NIR PL for at least 48 h with excellent tissue penetration in vivo. CUDZG is capable of glioblastoma (GBM) targeting and tumor homing. The tumor growth of both the orthotropic and subcutaneous GBM‐bearing mice is significantly suppressed by CUDZG.